Role of lung ultrasonography in the diagnosis of COVID-19 patients admitted to the emergency department - Şan, İshak (Notf Rett Med, 2020)
INTRODUCTION: In this study, the use of lung ultrasonography (LUS) to diagnosis lung findings was evaluated in patients with suspected COVID-19 who were admitted to the emergency department (ED). METHODS: This observational clinical study was conducted in the ED of the Ankara City Hospital during the period April 1–30, 2020. Patients who were admitted to the ED were triaged as COVID-19 infected and who agreed to undergo LUS/LCT (lung computed tomography) were included in the study. RESULTS: Included in the study were 40 patients who had been prediagnosed with COVID-19. Pneumonia was detected with LCT in 32 (80%) patients, while the LUS examination identified pneumonia in 23 patients. The most common finding in LCT was ground-glass opacity (n = 29, 90.6%). Of the 23 patients with pneumonia findings in LUS, 15 (65.2%) had direct consolidation. Among the 32 patients who were found to have pneumonia as a result of LCT, 20 (62.5%) had signs of pneumonia on LUS examination, and 12 had no signs of pneumonia. In addition, 3 patients showed no signs of pneumonia with LCT, but they were misdiagnosed with pneumonia by LUS. The sensitivity of LUS in the diagnosis of pneumonia in the COVID-19 patients was 62.5%, while its specificity was 62.5%. In addition, its positive predictive value was 87.0%, and its negative predictive value was 29.4%. CONCLUSION: LUS may also be used in the diagnosis of pneumonia in COVID-19 patients because it is a valuable and accessible bedside diagnostic tool. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10049-020-00807-3) shows RT-PCR results of patients with a definitive diagnosis of COVID-19 by lung computed tomography and patients with pneumonia detected by lung ultrasonography. The article and additional material are available at www.springermedizin.de. Please enter the title of the article in the search field. You will find the additional material under “Ergänzende Inhalte” in the article.